Feasibility of utilizing a commercial eye tracker to assess electronic health record use during patient simulation. (September 2016) - Gold, Jeffrey Allen; Stephenson, Laurel E; Gorsuch, Adriel; Parthasarathy, Keshav; Mohan, Vishnu
Numerous reports describe unintended consequences of electronic health record implementation. Having previously described physicians' failures to recognize patient safety issues within our electronic health record simulation environment, we now report on our use of eye and screen-tracking technology to understand factors associated with poor error recognition during an intensive care unit–based electronic health record simulation. We linked performance on the simulation to standard eye and screen-tracking readouts including number of fixations, saccades, mouse clicks and screens visited. In addition, we developed an overall Composite Eye Tracking score which measured when, where and how often each safety item was viewed. For 39 participants, the Composite Eye Tracking score correlated with performance on the simulation (p = 0.004). Overall, the improved performance was associated with a pattern of rapid scanning of data manifested by increased number of screens visited (p = 0.001), mouse clicks (p = 0.03) and saccades (p = 0.004). Eye tracking can be successfully integrated into electronic health record–based simulation and provides a surrogate measure of cognitive decision making and electronic health record usability.